2022
DOI: 10.3982/ecta19815
|View full text |Cite
|
Sign up to set email alerts
|

Tasks, Automation, and the Rise in U.S. Wage Inequality

Abstract: We document that between 50% and 70% of changes in the U.S. wage structure over the last four decades are accounted for by relative wage declines of worker groups specialized in routine tasks in industries experiencing rapid automation. We develop a conceptual framework where tasks across industries are allocated to different types of labor and capital. Automation technologies expand the set of tasks performed by capital, displacing certain worker groups from jobs for which they have comparative advantage. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 62 publications
(84 reference statements)
1
49
1
Order By: Relevance
“…More recent studies have distinguished between technology's task-displacement and task-reinstatement effects (where new technology increases the need for a wider array of labor-intensive tasks) (Acemoglu andRestrepo, 2018, 2019). Several studies have shown that automation technologies have resulted in wage inequality in the US, driven by relative wage declines for workers specializing in routine tasks (Autor et al, 2006;Van Reenen, 2011;Acemoglu and Restrepo, 2022b).…”
Section: The Economic Impacts Of Automation Technologiesmentioning
confidence: 99%
“…More recent studies have distinguished between technology's task-displacement and task-reinstatement effects (where new technology increases the need for a wider array of labor-intensive tasks) (Acemoglu andRestrepo, 2018, 2019). Several studies have shown that automation technologies have resulted in wage inequality in the US, driven by relative wage declines for workers specializing in routine tasks (Autor et al, 2006;Van Reenen, 2011;Acemoglu and Restrepo, 2022b).…”
Section: The Economic Impacts Of Automation Technologiesmentioning
confidence: 99%
“…Our multivariate research design is subject to other forms of endogeneity besides unobserved worker ability and worker-to-firm matching, such as changes in unobservable firm characteristics that impact both wages and financial reporting quality (e.g., Roberts and Whited [2013]). 24 We propose two settings to provide additional support of compensating wage Acemoglu et al [2022]) although we acknowledge that an error in this split variable can be correlated with wage trajectories. 24 One potential endogeneity issue is unobservable and correlated variation in the riskiness of a firm's projects, financial reporting quality, and returns to labor.…”
Section: Demise Of Arthur Andersenmentioning
confidence: 99%
“…Whereas the first narrative projects a general labor market "upgrading" due to digitalization, the second predicts a "de-routinization" accompanied by a "job polarization" of the labor market, as routine jobs tend to be located in the middle of the wage distribution and non-routine occupations at the upper and lower tails. While the literature focusing on the US labor market found convincing evidence supporting recent job polarization trends (e.g., Acemoglu & Restrepo, 2022;Autor et al, 2008;Goos & Manning, 2007;Goos et al, 2009), studies for Europe show considerable cross-country variation between general upgrading and polarization (see, e.g., Fernández-Macías, 2012;Kurer & Palier, 2019;Oesch & Piccitto, 2019;Oesch & Rodríguez Menés, 2011).…”
Section: Introductionmentioning
confidence: 99%